The Influence of Academic Ability, Financial Literacy, and Self-Control on the Personal Financial Management - Siti Barokah; Sri Ramlah; Wilson Candra Teguh Pratama; Desyia Aulia Madhani; Novia Evelyna (Citakonsultindo, 2024)
This study focuses on scholarship recipients because they have greater responsibility in managing personal finances. This is due to the funding coming from government or private budgets for education, and not all underprivileged students can enjoy it. Management students are already familiar with economic and financial concepts learned during lectures. This research uses an explanatory method and is conducted at Universitas Muhammadiyah Gombong. Data is collected through questionnaires and analyzed using the Statistical Package for Social Science (SPSS) version 25 and multiple linear regression analysis techniques. Data quality tests include validity and reliability tests, while classical assumption tests include normality tests, autocorrelation tests, multicollinearity tests, and heteroscedasticity tests. The t-test is used to measure the influence of an independent variable on the dependent variable, while the coefficient of determination (R²) is used to predict the contribution of independent variables to the dependent variable. This study aims to determine the influence of academic ability, financial literacy, and self-control on personal financial management and to see the differences in personal financial management between economics and non-economics students.